Small open reading frames (sORFs): Driving big improvements in plant development and quality - Kui Dong; Chaofan Shan; Dongyu Wen; Zifan Cui; Jun Cao (Plant Stress)
Small open reading frames (sORFs) are defined as short nucleotide sequences, typically no longer than 300 base pairs, which have the potential to encode small peptides. With the advent of sophisticated technologies such as bioinformatics, ribosome profiling, and mass spectrometry, the investigation of sORFs has experienced a transformative shift and significant expansion. This review provides a comprehensive analysis of the identification, categorization, functional mechanisms, and diverse roles of sORFs in plant development. In the plant, sORFs are pivotal components that enhance responses to both biotic and abiotic stresses by encoding small peptides that are either intricately involved in complex hormone regulation and signaling networks, or precisely regulate the expression of downstream resistance genes. The impact of sORFs extends well beyond stress resistance and they are also implicated in the developmental and physiological functions of plants. sORFs play a crucial role in determing the overall morphological architecture of plants, governing morphological changes throughout the plant life cycle, and are instrumental in regulating metabolite accumulation, which influences plant quality. The synergistic application of sORFs with gene editing technologies holds great promise, not only for devising novel strategies to improve plant quality, resulting in crops that are more resistant, nutrient-rich, and productive, but also for establishing innovative molecular breeding pathways. In summary, understanding and harnessing the potential of sORFs is a cutting-edge area of research that is poised to revolutionize the future of plant biology and agriculture, and ongoing exploration of their functions and mechanisms is anticipated to yield groundbreaking discoveries and practical applications in the future.